Thymidine exerts anti-doxorubicin-induced cardiomyopathy effect through the regulation of the PPAR signaling pathways and ferroptosis pathways - Li, Bin; Wang, Qifei; Zhou, Jiashuo; Li, Peihai; Sun, Chen; Xia, Qing; Zhang, Yun (Frontiers in Pharmacology, 2025)
IntroductionTo evaluate the anti-cardiomyopathic activity of thymine (Thy) and to elucidate its mechanism of action.MethodsTransgenic zebrafish with enhanced green fluorescent protein (EGFP)-labelled hearts (Tg (cmlc2: EGFP)) and wild-type AB zebrafish were used as experimental animals. A blank control group, a doxorubicin (DOX) model group, a dexrazoxane (DEX)-positive drug group and Thy drug treatment group were established. After treatment, indicators closely related to cardiac function, such as the pericardial area, heart rate, stroke volume, short-axis shortening (SAS) rate, and ejection fraction of the zebrafish in each group, were evaluated to determine the protective activity of Thy against DOX-induced cardiomyopathy. The regulatory roles of key genes in the pathways associated with the cardioprotective activity of Thy were analyzed via RT-qPCR.ResultsThe results indicated that Thy effectively relieved DOX-induced pericardial edema; reversed the effects of DOX on heart rate, stroke volume, SAS rate, ejection fraction, and blood flow velocity; and relieved DOX-induced myocardial ischemia, myocardial cell apoptosis and pathological structural changes in heart tissues. The RT‒qPCR results revealed that Thy regulated the mRNA expression levels of genes related to the PPAR signaling pathway and ferroptosis pathway (such as pparg, apoa1a, acsl5, pltp, and tfa).DiscussionThy may exert its anti-DOX-induced cardiomyopathy effect through the regulation of the PPAR signaling and ferroptosis pathways.